E-health, assistive technologies and applications for assisted living : challenges and solutions - Rocker, Carsten; Rocker, Carsten, 1975-; Ziefle, Martina, 1962- (Hershey PA : Medical Information Science Reference, 2011)
"This book reviews existing literature in assistive technologies and provides suggestions and solutions for improving the quality of assisted living facilities and residences through the use of e-health systems and services"--Provided by publisher.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Medical informatics; Assistive computer technology; Congregate housing